Exploring The Showrooming and Webrooming Effect on Hybrid Platform and Reselling Platform: The Strategic Role of In-Store Service - Yue, Bicheng; Yun, Qiaoyun; Liu, Bin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
This paper aims to examine how customers’ bi-directional free-riding behavior (showrooming phenomenon and webrooming phenomenon) affects the operation of e-commerce platforms and how the service resources of different platforms can be coordinated to bring a better shopping experience to consumers. We develop a game model based on a multi-channel supply chain structure to explore competitive decisions, cooperative decisions, and coordinative decisions, respectively, where the hybrid platform and the reselling platform engage in both price and service competition. It shows that whichever platform actively enhances service efforts is beneficial to the development of the entire supply chain system, especially for its own more significant promotion. However, when there are increasing numbers of bi-directional free-riding customers in the market, both e-commerce platforms are becoming conservative, and are waiting for the other side to enhance its service efforts. On this basis, a coordination mechanism can achieve a win-win situation for both platforms, where the profit of the two platforms, total consumer surplus, and total social welfare are higher than the level before the implementation of coordination.